Penerapan Sistem Informasi Pendaftaran pada TK Aba Kampung Padang Berbasis Web - Laurensa, Ayu; Gultom, Manorang; Tendean, Sandi (Journal of Information System and Education Development, 2025)
By utilizing the use of website-based technology can provide convenience for schools in the registration process and class data processing. The author uses a descriptive method as a research  design. Data collection  techniques  by conducting  interviews,  observations  and literature study. In addition, the technique used in designing the system in this research is to use object-oriented techniques with modeling Unified Modeling Language (UML). The results of  this  study  are  a  website-based   registration  information   system  at  Cahaya  Berseri Kindergarten which is used to facilitate the online registration process and make it easier for admins to manage classes and make it easier to print class reports. The conclusion is that the existence of this proposed system can facilitate the registration process, class arrangement and homeroom placement to be more effective and efficient. Suggestions from the authors of the proposed system are developing a system by creating features for registration payments, developing a system so that the website looks more attractive, developing a class arrangement system  and  homeroom  placement  for  large  numbers  of  students,  keeping  confidential information  on the website safe so that avoiding  fraud that can harm certain parties and maintaining the website so that there are no errors in the system